Drying behaviour of Andrographis paniculata in vacuum drying - Hee, Yen Yi; Chong, Gun Hean (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2015)
Hempedu bumi (Andrographis paniculata, AP), also known as the king of bitters, is an herb commonly found in Asian communities for medicinal usage. The drying behaviour of AP at temperatures of 40, 50, and 60°C with vacuum pressures of 10 and 30 kPa was investigated in this study. The data were then fitted with semi-theoretical and theoretical thin-layer drying models. The results reveal that the drying time is significantly (p<0.05) affected by temperature and pressure. A two-term, thin-layer model was determined as the most suitable model to fit the drying behaviour of AP. The effective diffusivity and active energy for moisture diffusion were 10-13 m2/s and 33.4 kJ/mol, respectively.